Usefulness of PET With [18F]LBT-999 for the Evaluation of Presynaptic Dopaminergic Neuronal Loss in a Clinical Environment - Ribeiro, Maria-Joao; Vercouillie, Johnny; Arlicot, Nicolas; Tauber, Clovis; Gissot, Valérie; Mondon, Karl; Barantin, Laurent; Cottier, Jean-Philippe; Maia, Serge; Deloye, Jean-Bernard; Emond, Patrick; Guilloteau, Denis (Frontiers in Neurology, 2020)
Purpose: It is of great interest to distinguish syndromic entities with impairment of the nigrostriated dopaminergic system such as Parkinson’s disease (PD), from those without impairment like essential tremor or iatrogenic extrapyramidal syndrome due to prolonged neuroleptic therapy. The density of neuronal dopamine transporter (DAT) is directly correlated with the dopamine system injury. Although many positron emission tomography (PET) and single-photon emission computerized tomography (SPECT) DAT radioligands have been developed, only 123I-FP-CIT for SPECT is currently used in clinical routine. In this preliminary study the contribution of a new PET DAT radioligand in routine clinical environment, the 18F-LBT-999, was evaluated. Material and Methods: 8 controls and 6 PD patients were included. Ninety-minute dynamic PET following an intravenous injection of 18F-LBT-999 were acquired. Time activity-curves (TAC), binding potential (BP) using the simplified reference tissue model (SRTM), and ratios obtained for a 10-min image, acquired between 30 and 40 minutes post-injection (pi), were calculated in the caudate nucleus and in the putamen, using regions of interest (ROI) defined over each T1 3-D magnetic resonance imaging (MRI). For both BP and ratios, the cerebellum activity was used as non-specific reference region. Results: 18F-LBT-999 showed good brain uptake and regional distribution according to known DAT density for striatum. In PD patients, striatal uptake was lower than in controls which is evidenced by. BP and ratios calculated for both striatal nuclei, significantly lower in PD patients compared to controls (p<0.001). Conclusions: 18F-LBT-999 is a promising PET DAT radioligand. It is demonstrated that the use of a 10-min PET acquisition is reliable to differentiate PD patients from controls. This allows that it be used in any Nuclear Medicine Department equipped with a PET/CT tomograph.